PENGARUH MEDIA SOSIAL TERHADAP MINAT BACA GENERASI Z (SURVEY PADA FOLLOWERS AKUN TWITTER MEDIA @CNNINDONESIA) - Fatimah Nur’ainani Hidayat; Nurseri Hasnah Nasution; Ahmad Harun Yahya (Program Studi Jurnalistik, Universitas Islam Negeri Raden Fatah Palembang, 2021)
Social media is one of many technology developments which already common in human’s life, especially for generation Z whom half of the daily works are done with the help of social media. Social media is stated as one factor that influence the development of children’s behaviour, also to human’s reading interest. In the certain amount of frequency and quality of use of social media is considered capable of influencing one’s reading interest and reading quality. This research was aimed to find out the influence of social media towards generation Z’s reading interest. The sample used in this research was generation Z whom followers of one media company, CNN Indonesia (@CNNIndonesia) on twitter with purposive sampling technique. Keywords: Social Media, Reading Interest, Generation Z